Two-incision laparoscopic cholecystectomy performed via the "marionette" technique versus conventional laparoscopic cholecystectomy in pediatrics - Mohamed A. Shehata; Abdelmotaleb E. Ebeid; Ashraf A. El Attar (SpringerOpen, 2020)
Abstract Background Laparoscopic cholecystectomy (LC) has considered the gold standard for the treatment of symptomatic gallstones. The "marionette" technique is a surgical technique for performing a safe, two-incision laparoscopic cholecystectomy without the use of an additional port or any new access devices. This study aimed to compare between the cost and outcome of two incisions LC performed via the marionette technique and the standard LC in pediatrics. Results All 32 children with symptomatic cholecystolithiasis were discharged from the hospital in the first postoperative day with no statistically significant difference within days to return to normal work (p = 0.607). The operative time in the group (A) which included 16 children who underwent 2 incisions marionette style LC technique was non-significantly longer time (p = 0.184) than the group (B) which included 16 children who underwent conventional 4 incisions LC technique. Visual analog scores for pain showed a significant difference between both groups at 6 h and 12 h postoperative (p = 0.000 and 0.003, respectively). Overall patient in marionette group was very satisfied by fewer incision and better cosmesis. Conclusion Marionette technique performed by an experienced surgeon among pediatric shows a statistically significant cost benefit while maintaining good operative time, less postoperative pain, and more patient's satisfaction and provides excellent aesthetic results.